Porcine epidermal stem cells as a biomedical model for wound healing and normal/malignant epithelial cell propagation - Motlík, J; Klíma, J; Dvoránková, B; Smetana, K (Theriogenology, 2007)
This article summarizes research using cells derived from epidermis of the miniature pigs for use as a cell therapy for skin repair and as a model for squamous carcinoma of the head and neck. Stem cells are an important "tool" for biomedical research. Adult stem cells are defined functionally, as cells that have the capacity to self-renew as well as the ability to generate differentiated cells. They are present in defined tissue microenvironments called niches. Asymmetric mitosis allows them to produce one daughter cell with the properties of stem cells (self-renewal) and a second cell with characteristics of progenitor cells, or transit amplifying cells, which proliferate quickly but with a limited number of mitotic divisions. Porcine epidermal stem cells, located in the bulge region of the outer root sheath of hair follicles, migrate in vitro from hair sheaths and because they are resistant to anoikis (detachment induced apoptosis), survive in non-adhesive conditions to form spheroids. These cells express keratins, galectin-1 and their nuclei are rich in DeltaNp63alpha. Interestingly, the multiple phenotype analysis of the human tumor cells in squamous carcinoma of head and neck revealed similarities with epidermal stem cells. These cancer stem cells are usually located on the periphery of the tumor where the invasive front of the tumor responsible for its aggressive behavior is located. In contrast, extensive expression of markers of terminal differentiation such as expression of glycoligands reactive for the endogenous lectin, galectin-3, indicates better tumor prognosis.
Keywords: Stem Cell Transplantation; Animals; Stem Cells; galektin 1; Keratins; Wound Healing; Epidermal Cells; nádory hlavy a krku; lidé; epidermální buňky; transplantace kmenových buněk; keratiny; prasata; kmenové buňky; vlasový folikul; Mitosis; Galectin 1; mitóza; Hair Follicle; Head and Neck Neoplasms; Swine; hojení ran; Cell Survival; zvířata; viabilita buněk; Humans